Notre monde brûle. - Danesi, Fabien; Arab Museum of Modern Art, Doha; Palais de Tokyo, Paris; Grossi, Frédéric; Karroum, Abdellah
Avec / With : Inji Efflatoun ; Kahlil El Ghrib ; Faraj Daham ; Shirin Neshat ; John Akomfrah ; Francis Alÿs ; Fabrice Hyber ; Tania Bruguera ; Mounir Fatmi ; Kader Attia ; Yto Barrada ; Wael Shawky ; Katia Kameli ; Michael Rakowitz ; Amal Kenauwy ; Otobang Nkanga ; Younes Rahmoun ; Danh Vo ; Amina Menia ; Ben Russell ; Basim Magdy ; Mounira Al Solh ; Sammy Baloji ; Jane Kin Kaisen ; Oriol Vilanova ; Mustapha Akrim ; Asli Cavusoglu ; Monira Al Qadiri ; Sophia Al Maria ; Dominique Hurth ; Bady Dalloul ; Sara Ouhaddou ; Bouthayna Al Muftah ; Raqs Media Collective.
This book is published on the occasion of the exhibition "Our world is Burning", "Notre monde brûle", conceived in collaboration with Mathaf : Arab Museum of Modern Art, Doha and presented at the Palais de Tokyo, Paris, 21.02 - 17.05.2020
boek